The Intensity of Hospital Care Utilization by Dutch Patients With Lung or Colorectal Cancer in their Final Months of Life. (30th April 2019) - de Man, Yvonne; Atsma, Femke; Oosterveld-Vlug, Mariska G.; Brom, Linda; Onwuteaka-Philipsen, Bregje D.; Westert, Gert P.; Groenewoud, A. Stef
Understanding the overuse and underuse of health-care services in the end-of-life (EoL) phase for patients with lung cancer (LC) and colorectal cancer (CRC) is important, but knowledge is limited. To help identify inappropriate care, we present the health-care utilization profiles for hospital care at the EoL of patients with LC (N = 25 553) and CRC (N = 14 911) in the Netherlands between 2013 and 2015. An administrative database containing all in-hospital health-care activities was analyzed to investigate the association between the number of days patients spent in the emergency department (ED) or intensive care unit (ICU) and their exposure to chemotherapy or radiotherapy. Fewer patients received hospital care as death neared, but their intensity of care increased. In the last month of life, the average numbers of hospital bed days, ICU days, and ER contacts were 9.0, 5.5, and 1.2 for patients with CRC, and 8.9, 6.2 and 1.2 for patients with LC in 2015. On the other hand, the occurrence of palliative consultations ranged from 1% to 4%. Patients receiving chemotherapy 6 months before death spent fewer days in ICU than those who did not receive this treatment (odds ratios: CRC = 0.6 [95% confidence interval: 0.4-0.8] and LC = 0.7 [0.5-0.9]), while those receiving chemotherapy 1 month before death had more ED visits (odds ratios: CRC = 17.2 [11.8-25.0] and LC = 15.8 [12.0-20.9]). Our results showed that patients who were still receiving hospital care when death was near had a high intensity of care, yet palliative consultations were low. Receiving chemotherapy or radiotherapy in the final month of life was significantly associated with more ED and ICU contacts in patients with LC.